Neonatal lupus: clinical features and risk of congenital cardiac heart block in newborns from mothers with anti Ro/SSA antibodies - M. Frassi; A. Brucato; I. Cavazzana; F. Franceschini; D. Faden; M. Motta; A. Doria; R. Cimaz; M.P. Pisoni; M. Muscarà; G. Castellino; G. Brambilla; et al. (PAGEPress Publications, 2001)
Objective: To assess the prevalence of Congenital Heart Block (CHB) in newborns from anti Ro/SS-A antibodies positive mothers affected by connective tissue diseases (CTD) and to evaluate the prevalence of other manifestations of Neonatal Lupus (NL) and the electrocardiographic abnormalities. Methods: A prospective study was conducted on 100 anti Ro/SS-A positive mothers that were followed before and during their 118 pregnancies (4 twin pregnancies and 18 second pregnancies). Counterimmunoelectroforesis (CIE) and immunoblot (IB) were used to test antibodies to extractable nuclear antigens (ENA). Results: Only 2 cases of CHB (1.8%) were found among the 112 living newborns. In one case the mother with primary Sjögren's Syndrome (pSS) was anti Ro 60 and 52kD positive while in the other case the mother affected by undifferentiated connective tissue disease (UCTD) was anti Ro 60kD and anti La positive. No fetal death was due to CHB. There were no cutaneous rashes at birth while mild hepatic enzyme alterations were observed in 21 (68%) of the 31 tested newborns. In 22 healthy newborns an ECG have been registered and in 4 cases (18.2%) sinus bradycardia was found. During the follow up 7 suckling showed Cutaneous Neonatal Lupus. Moreover a six month girl developed Kawasaki Syndrome. Conclusions: The risk of delivering a child with CHB is 1.8% in anti Ro/SS-A positive mothers with CTD. This finding is extremely important in the preconceptional counseling of anti-Ro/SS-A positive women. Furthermore mild electrocardiographic abnormalities may be found in their healthy newborns.